Prevalence and Characteristics of Pregnant Women With Urinary Incontinence at Rika Amalia Hospital Palembang - Juenli, Angelica; Fauzi, Amir; Putra, Hadrians Kesuma; Krisna, Ratih; Nurwany, Raissa (Biomedical Journal of Indonesia, 2025)
Introduction. Urinary incontinence (UI) is the involuntary discharge of urine. UI is often not reported due to social stigma and public relief. In addition, UI is a non-life-threatening condition so people consider UI as a nuisance and not a health problem. This shows the need for promotive and preventive efforts so that patients can immediately seek medical treatment and prevent UI. This study aims to identify the prevalence and characteristics of pregnant women with UI at Rika Amalia Hospital Palembang. Methods. This study is an observational descriptive research with a cross-sectional research design using primary data by filling out questionnaires and direct interviews with pregnant women at Rika Amalia Hospital Palembang. Results. This study involved 73 pregnant women. Most UI cases were at the age of <35 years (88%), education level ≤12 years (68%), no smoking behavior (100%), no caffeinated beverage consumption behavior (96%), third trimester (60%), multipara (40%), vaginal delivery (56%), BMI ≥ 25 kg/m2 (56%), no history of constipation (60%), no history of UI before pregnancy (92%), and had no family history of UI (88%). Conclusion. The prevalence of pregnant women with UI at Rika Amalia Hospital Palembang from August to October 2024 is 34.2%. Most UI cases happened in pregnant women with the age of <35 years, education level ≤12 years, no smoking behavior, no caffeinated beverage consumption behavior, third trimester, multipara, vaginal delivery, BMI ≥ 25 kg/m2, no history of constipation, no history of UI before pregnancy, and no family history of UI.